Transportable environments : theory, context, design, and technology : papers from the International Conference on Portable Architecture, London, 1997 - Kronenburg, Robert (E & Fn Spon, 1998)
Transportable Environments explores aspects of the historical and theoretical basis for portable architecture and provides an insight into the wide range of functions that it is used for today, the varied forms that it takes and the concerns and ideas for its future development. Written by a team of international commentators, this volume provides a state-of-the-art survey of this specialist area and will be of interest to a wide range of professionals across the construction and design industries.